Inositols: from established knowledge to novel approaches - Dinicola, Simona (2021)
Myo-inositol (myo-Ins) and D-chiro-inositol (D-chiro-Ins) are natural compounds involved in many biological pathways. Since the discovery of their involvement in endocrine signal transduction, myo-Ins and D-chiro-Ins supplementation has contributed to clinical approaches in ameliorating many gynecological and endocrinological diseases. Currently both myo-Ins and D-chiro-Ins are well-tolerated, effective alternative candidates to the classical insulin sensitizers, and are useful treatments in preventing and treating metabolic and reproductive disorders such as polycystic ovary syndrome (PCOS), gestational diabetes mellitus (GDM), and male fertility disturbances, like sperm abnormalities. Moreover, besides metabolic activity, myo-Ins and D-chiro-Ins deeply influence steroidogenesis, regulating the pools of androgens and estrogens, likely in opposite ways. Given the complexity of inositol-related mechanisms of action, many of their beneficial effects are still under scrutiny. Therefore, continuing research aims to discover new emerging roles and mechanisms that can allow clinicians to tailor inositol therapy and to use it in other medical areas, hitherto unexplored. The present paper outlines the established evidence on inositols and updates on recent research, namely concerning D-chiro-Ins involvement into steroidogenesis. In particular, D-chiro-Ins mediates insulin-induced testosterone biosynthesis from ovarian thecal cells and directly affects synthesis of estrogens by modulating the expression of the aromatase enzyme. Ovaries, as well as other organs and tissues, are characterized by a specific ratio of myo-Ins to D-chiro-Ins, which ensures their healthy state and proper functionality. Altered inositol ratios may account for pathological conditions, causing an imbalance in sex hormones. Such situations usually occur in association with medical conditions, such as PCOS, or as a consequence of some pharmacological treatments. Based on the physiological role of inositols and the pathological implications of altered myo-Ins to D-chiro-Ins ratios, inositol therapy may be designed with two different aims: (1) restoring the inositol physiological ratio; (2) altering the ratio in a controlled way to achieve specific effects.